Couplonics Of Cyclic Ternary Systems: From Coupled Periodic Waveguides To Discrete Photonic Crystals - Boucher, Y. G. (Advanced Electromagnetics, 2013)
In the context of coupled periodic waveguides, "couplonics" refers to the rigorous equivalence between continuous wave coupling and localized interactions. We extend it here to a cyclic ternary system, looked upon as the simplest discrete photonic crystal with actual periodic boundary conditions. A linear decomposition on a supermode basis enables one to reduce the original sixwave problem to three independent two-wave distributed Bragg reflectors (or 1D PC).